Optimization of the Role of Waqf Bank Micro in Access to Financing, Developing Human Resources Skills, and Financial Literacy on MSME Performance to Improve MSME’s Capital in Surabaya - Diana Mukhbitah Sary; Tri Andjarwati; Riyadi Nugroho (Harmony Management: International Journal of Management Science and Business, 2025)
Study This analyze the role of Waqf Bank Micro (BWM) in increase performance of MSMEs in Surabaya, with capitalization as variable mediation . Focus main covers access financing , human resource development, and literacy finance, using approach quantitative through survey against 90 MSME actors fostered by BWM Al- Fithrah Wava Mandiri . Analysis using SEM with SmartPLS 4.0 shows that third variable influential significant to performance of MSMEs, both in a way direct and through capitalization . Capitalization become the most dominant mediator ( coefficient 0.581; p-value 0.000). Findings This confirm role BWM doubles as institution financing and empowerment . In theoretical , results This support theory Resource-Based View (RBV) and its importance financing accompanied by strengthening capacity business in a way holistic.